Desarrollo de una aplicación web para control de la inversión sobre actividades de mercadeo en MMS (Marketing Management System). (2018)
The specific idea of this project was to develop a web application that could manage the inventory of pop material (point of purchase) and the expenses of the marketing activities of the company Apex Tool Group S.A.S. The company in question suffered from a system that would allow the Trade Marketing team to visualize, document and control in real time the investment and the return that will be achieved with the Trade activities in the clients; this included placement, evacuation and incentive plans. The application in question had as an initial phase the lifting of the requirements corresponding to the system to be developed., And as subsequent phases, design and develop a web tool in which the sales and marketing areas could interact, evaluate the web application based on a Test Plan, and as a final phase, implement the tool in a productive and functional environment. Due to the above considerations, and in virtue of advancing the web application, the Scrum methodology was partially used in the modeling, testing and development process; in effect, this system was chosen because it was an agile and scalable work method, characteristics that easily allowed the integration of equipment, fault detection, inclusion of requests and tests through a series of periodic revisions called "Sprints", which were carried out progressively with the client's team, until the culmination of the project. In relation to the latter, the project was divided into four (4) basic stages based on the Scrum architecture detailed below: Design: Meetings were held with each of the areas involved (Marketing, Trade and IT) in the process, with the purpose of understanding the functional and non-functional requirements of the project and its scope. Construction: The project was executed under a collaborative model through Team Foundation Server , each of the developers will work under the IDE of Visual Studio generating progress as it is proposed in the schedule; Testing: The test plan was fulfilled to validate the functionalities and possible corrections directly with the users; Feedback: In this final stage, the findings and contingencies found during the process were documented, a process led by a mediator between the development team and the project stakeholders